Enhanced Microwave Absorption Performance from Magnetic Coupling of Magnetic Nanoparticles Suspended within Hierarchically Tubular Composite. (6th May 2019) - Wu, Zhengchen; Pei, Ke; Xing, Linshen; Yu, Xuefeng; You, Wenbin; Che, Renchao
Abstract: The microwave absorption (MA) performance of carbon materials is severely hindered by their drawbacks of lacking magnetic loss ability and mismatched electromagnetic impedance. In this work, utilizing sustainable biomass kapok as a template, the hierarchically tubular C/Co nanoparticle composite is rationally constructed to acquire the enhanced MA performance for the first time. The fruit‐tree‐like hierarchical structure is composed from a "trunk" of kapok‐derived carbon microtubes, a "branch" of entangled carbon nanotubes, and "fruit" of Co nanoparticles embedded in the nanotubes. Such a hierarchically tubular structure offers the composite: i) a submillimeter‐scale 3D magnetic coupling network and reinforced magnetic loss ability, ii) a hierarchical dielectric carbon network, iii) better matched impedance, confirmed by the off‐axis electron holography and micromagnetic simulation. Accordingly, the as‐prepared hierarchically tubular carbon composite demonstrates impressive MA performance, with a maximum reflection loss of as much as −52.3 dB and a broad absorption bandwidth of 5.1 GHz. These encouraging achievements light the way to the development of the hierarchical microstructure of magnetic absorbents. Abstract : This hierarchically tubular composite is rationally designed with a sustainable kapok template. Benefiting from the submillimeter‐scale magnetic coupling network and hierarchical conductive path, the hierarchical composite demonstrates a first‐rate microwave absorption performance.